(3GdNHQ GdeYQH Yf GdCeQ GdeZQH GdMGd HGdCfOdS hKZhQ GdeZQHs - (3eMeO CHj QGS Hf CMeO Hf YHO GdbGOQ GdfGUQj,J (B1239 (3g` s
(3ChdgG (B:s
(3MeOkG ddaGYd aj Ndbg eGojQjO , hHGdfUQ hGdNPdGf aQjO s
(3BNQgG (B:s
(3heYfi dnHi(B: (3CLGH heYfi(B: (3de jJS (B: (3hde jbJO Hef bHdg s
(3hSeGg aj HQhcdef (B: (3GdbUU GdeZQH Yf GdNHQ GdeYQH YeG hbY HGdCfOdS hKZhQ GdeZQH (B"s
(3hgh cJGH aj PcQ eGLQi ddeSdejf eY GdcaGQ aj GdYOhI hGdCfOdSs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B18 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B25s
Keywords: (3GdJGQjNs